From Writing for Computers to Writing with Computers - A heroic tale (KULT_online, 2014)
Till A. Heilmann's monograph, Textverarbeitung. Eine Mediengeschichte des Computers als Schreibmaschine examines the development of contemporary writing on computers. Additionally, by using these media, he reflects critically on the historical reconstruction of the (pre)history of word processing or rather the historical processes of coupling computers with keyboards and screens, and on the close relationship between computers and writing.